2020
DOI: 10.26911/jepublichealth.2020.05.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Effect of COVID 19 Pandemic on the Utilization of Maternal Newborn Child Health and Nutrition Services in Somali Region of Ethiopia

Abstract: Background: Somali Region of Ethiopia recorded the first confirmed case of SARS-CoV-2 (COVID 19) pandemic on 26 th April 2020. The study aimed to assess the effect of the pandemic on the utilization of maternal newborn, child and nutrition health services. Subjects and Method: This was a retrospective chart review of monthly DHIS database of health facilities in Farfan zone of Somali Region and test of association using t test was used to compare the mean reduction in utilization of maternal and child health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A mixed method study in eight health facilities in Ethiopia comparing the service utilisation trends in the rst 6 months of COVID-19 with the corresponding time and data points of the preceding year showed reduced ANC visits (208.9 to 181.7/month, p=0.433) and under 5 visits (225.0 to 139.8/month, p=0.007) [8]. An assessment of effect of the pandemic on the uptake of MHC in Somali region of Ethiopia, through a retrospective chart review revealed that the mean number of ANC pre-pandemic was 4088 and intra-pandemic was 3498., a 14% decline in ANC attendance [39] . This decline in ANC visits was corroborated by a national study using reproductive, maternal, and newborn health services data from governmental health facilities in Ethiopia during a similar time period [11].…”
Section: Covid Concerns and Psychologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed method study in eight health facilities in Ethiopia comparing the service utilisation trends in the rst 6 months of COVID-19 with the corresponding time and data points of the preceding year showed reduced ANC visits (208.9 to 181.7/month, p=0.433) and under 5 visits (225.0 to 139.8/month, p=0.007) [8]. An assessment of effect of the pandemic on the uptake of MHC in Somali region of Ethiopia, through a retrospective chart review revealed that the mean number of ANC pre-pandemic was 4088 and intra-pandemic was 3498., a 14% decline in ANC attendance [39] . This decline in ANC visits was corroborated by a national study using reproductive, maternal, and newborn health services data from governmental health facilities in Ethiopia during a similar time period [11].…”
Section: Covid Concerns and Psychologicalmentioning
confidence: 99%
“…Studies in both Somalia and Ethiopia recorded over a 20% decrease in skilled birth attendant births [11,39]. A study in six regions of Ethiopia covering 91% of the population, found that a 77% reduced risk of facilitybased births during the pandemic compared to pre-pandemic compared to pre-COVID among urban women but no difference in facility-based births among rural women [26].…”
Section: Covid Concerns and Psychologicalmentioning
confidence: 99%
“… Oladeji O., Oladeji B., Farah A.E., et al, 2020. Ethiopia [ 37 ] Assess effect of the pandemic on the utilization of MNCH health services. Quantitative retrospective chart review January–March 2020, April–June 2020.…”
Section: Resultsmentioning
confidence: 99%
“…A mixed method study in eight health facilities in Ethiopia comparing the service utilisation trends in the first 6 months of COVID-19 with the corresponding time and data points of the preceding year showed reduced ANC visits (208.9 to 181.7/month, p = 0.433) and under 5 visits (225.0 to 139.8/month, p = 0.007) [ 8 ]. An assessment of effect of the pandemic on the uptake of MHC in Somali region of Ethiopia, through a retrospective chart review revealed that the mean number of ANC pre-pandemic was 4088 and intra-pandemic was 3498., reflecting a 14% decline in ANC attendance [ 37 ] . This decline in ANC visits was corroborated by a national study using reproductive, maternal, and newborn health services data from governmental health facilities in Ethiopia during a similar time period [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation